Conservative Approach: Using Decompression Procedure for Management of a Large Unicystic Ameloblastoma of the Mandible - Xavier, Samuel Porfirio; Mello-Filho, Francisco Verissimo de; Rodrigues, Willian Caetano [UNESP]; Sonoda, Celso Koogi [UNESP]; Melo, Willian Morais de [UNESP] (Lippincott Williams & Wilkins, 2014)
Ameloblastoma is a relatively uncommon benign odontogenic tumor, which is locally aggressive and has a high tendency to recur, despite its benign histopathologic features. This pathology can be classified into 4 groups: unicystic, solid or multicystic, peripheral, and malignant. There are 3 variants of unicystic ameloblastoma, as luminal, intraluminal, and mural. Therefore, in mural ameloblastoma, the fibrous wall of the cyst is infiltrated with tumor nodules, and for this reason it is considered the most aggressive variant of unicystic ameloblastomas. Various treatment techniques for ameloblastomas have been proposed, which include decompression, enucleation/curettage, sclerotizing solution, cryosurgery, marginal resection, and aggressive resection. Literature shows treatment of this lesion continues to be a subject of intense interest and some controversy. Thus, the authors aimed to describe a case of a mural unicystic ameloblastoma of follicular subtype in a 19-year-old subject who was successfully treated using conservative approaches, as decompression. The patient has been followed up for 3 years, and has remained clinically and radiographically disease-free.
Keywords: Ameloblastoma; decompression; jaw neoplasms; unicystic; recurrence; treatment